Emotional (dys)Regulation and Family Environment in (non)Clinical Adolescents’ Internalizing Problems: The Mediating Role of Well-Being - Raposo, Beatriz; Francisco, Rita (Frontiers in Psychology, 2022)
Adolescence is a period of several changes and a time when young people are confronted with some difficult tasks of dealing with a diversity of emotions and building their own identity. Therefore, it is a period of higher vulnerability for the development of internalising problems. The present paper aims to study some constructs considered relevant to adolescents’ adjustment and/or internalising disorders, emphasising the role of well-being, emotional regulation and family environment. Therefore, this research aims to 1) test the mediating role of well-being in the relationship between emotional regulation difficulties, the family environment, and internalising problems, and 2) understand the differences between adolescents with a higher and lower risk of presenting internalising problems. In the study, 723 adolescents of both sexes (12-18 years old) from middle to high school completed self-report questionnaires. The results indicated that the mediating role of well-being was partially established between emotional regulation difficulties and internalising problems, explaining 31% of the variance in these problems. Well-being was also considered a partial mediator between family environment (cohesion and support and conflict) and internalising problems, explaining 19% and 26% of the variance, respectively. Furthermore, the group with a higher risk of developing internalising problems (n = 130) revealed higher levels of emotional regulation difficulties and family conflict. In contrast, this group reported less family cohesion and support and lower levels of well-being. The main results of the present study provide relevant data in the context of clinical practice. Important implications are also discussed for the design of psychopathology prevention programs and the promotion of global well-being with adolescents. Considering the limitations of the present study, such as the nonrandom sampling process and the reduced number of participants included in the clinical group, these results need to be deepened in future research in this area.